Ukrainian crisis: origins, consequences and prospects - M. A. Neimark (Проблемы постсоветского пространства)
The internationalization of the Ukrainian crisis and the “Ukrainization” of the international agenda have exposed the deep goals and strategic aspirations of the West, led by the United States, in modern geopolitics. The American strategic claim to organize the world order at its own discretion and the excessive conviction in its overestimated ability to be an unchanging world hegemon are causing a systemic failure. Its flip side is a sharp increase – through the prism of the events in Ukraine – in confrontational rhetoric and political, sanctions-economic and military-strategic activity against Russia, which have reached peak values. The Ukrainian crisis has become not only a bifurcation milestone in the development of world political processes, but also a new milestone in understanding and rethinking transformational shifts, divisions and isolations in global politics. Today, their unusually sharp critical assessments and conclusions are no longer isolated in the Western-centric discourse, which, we emphasize, have a tendency to increase in quantity and have a more clearly expressed qualitative content than before. Thus increasing the degree of predictive and evaluative accuracy of specialized analytical reflection, which initially assumes taking into account underestimated or, conversely, overestimated factors, circumstances and event flows in world politics.